Compensation and Production in Family Medicine by Practice Ownership - Alison C. Essary; Ellen P. Green; David N. Gans (SAGE Publishing, 2016)
The increasing focus on high performance, patient-centered, team-based care calls for a strategy to evaluate cost-effective primary care. The trend toward physician practice consolidation further challenges the primary care health care system. Productivity measures establish provider value and help inform decision making regarding resource allocation in this evolving health care system. In this national survey of family medicine practices, physician assistant (PA) productivity, as defined by mean annual patient encounters, exceeds that of both nurse practitioners (NPs) and physicians in physician-owned practices and of NPs in hospital or integrated delivery system-owned practices. Total compensation, defined as salary, bonus, incentives, and honoraria for physicians, is significantly more compared to both PAs and NPs, regardless of practice ownership or productivity. Physician assistants and NPs earn equivalent compensation, regardless of practice ownership or productivity. Not only do these data support the value and role of PAs and NPs on the primary care team but also highlight differences in patient encounters between practice settings. Rural and underserved community practices, where physician-owned practices persist, also merit further consideration. Further research is needed to inform both organizational and policy decisions for the provision of high-quality, cost-effective, and accessible primary health care.